Dynamic processing of DOM: Insight from exometabolomics, fluorescence spectroscopy, and mass spectrometry. Issue 3 (25th April 2018) - Smith, H. J.; Tigges, M.; D'Andrilli, J.; Parker, A.; Bothner, B.; Foreman, C. M.
Abstract: Dissolved organic matter (DOM) in freshwater environments is an important source of organic carbon, supporting bacterial respiration. Frozen environments cover vast expanses of our planet, with glaciers and ice‐sheets storing upwards of 6 petagrams of organic carbon. It is generally believed that DOM liberated from ice stimulates downstream environments. If true, glacial DOM is an important component of global carbon cycling. However, coupling the release of DOM to microbial activity is challenging due to the molecular complexity of DOM and the metabolic connectivity within microbial communities. Using a single environmentally relevant organism, we demonstrate that processing of compositionally diverse DOM occurs, but, even though glacially derived DOM is chemically labile, it is unable to support sustained respiration. In view of projected changes in glacier DOM export, these findings imply that biogeochemical impacts on downstream environments will depend on the reactivity and heterogeneity of liberated DOM, as well as the timescale.